Optical fluoroassays based on substrate induced quenching - Quantrill, Nigel Stuart Michael (Cranfield University, 1995)
The recently proposed bioassay procedure that is based on the substrate induced quenching (SIQ) of an indicator fluorescence for the measurement of analyte concentrations is evaluated. In this type of assay a enzynatic reaction and a fluorescence quenching interaction are coupled together. Typically, an appropriate dehydrogenase enzyme reduces or oxidises the nicotinamide adenine dinucleotide cofactor. The change in the concentration of NADH results in variations in the excited fluorophore population as observed through fluorescence intensity. This latter aspect is used to monitor substrate (analyte) concentrations. Results on the investigation of the substrate induced quenching bioassay method and possibilities of using it as the basis of (i) a novel enzyme bioassay technique and (ii) a novel bioprobe format are presented. Ethanol was chosen as the model analyte, and a new assay procedure for its measurement was developed. A generic theoretical relation is discussed for the observed assay kinetics of substrate induced quenching (SIQ) and a model is described that includes the effects due to dynamic/static quenching of the fluorophore by either the enzyme substrate or product. The validity of the derived model is shown by comparison with experimental results for a SIQ based ethanol assay. The option of running the dehydrogenase reaction so as to consume NADH rather than generate it is also investigated. In order to demonstrate this approach acetaldehyde was chosen as the model analyte, and a assay procedure for its measurement was developed. The potential of the SIQ technique for incorporation into biosensor based upon a 'reservoir' format was demonstrated through the development of custom optical instrumentation and resevoir flowcell. Applicability of the SIQ technique to other biosensor formats such as flow-injection analysis and 'dry reagent' technology is discussed. The overall applicability of the SIQ technique is assessed through the generation of a number of SIQ assays on the following substrates: ethanol, glucose, glucose-6- phosphate, L-glutamic acid, isocitric acid, acetaldehyde, pyruvic acid, ot-ketoglutaric acid, and oxalacetic acid.